2017
DOI: 10.5455/javar.2017.d184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol benzoate injection to male rabbits on glucose, total protein, albumin, calcium concentrations and prostate tissue

Abstract: Objective: This study was carried out to investigate the effects of estradiol benzoate (EB) injection to male rabbits on glucose, total-protein, albumin, calcium concentrations and prostate tissue, and the role of prolactin as an important mediator of estrogen action in prostate. Materials and methods: Fifty four adult male rabbits were used in this study. The rabbits were randomly divided into two groups. Group A contained 36 male rabbits, which were further randomly divided into four sub-groups, three of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Bromocriptine is used to treat infertility, hypogonadism, and ovarian hyperstimulation syndrome, benign tumors produced in the pituitary gland, adrenal gland, and thyroid gland. In reviewing 2014, it was shown that bromocriptine used to suppress milk production after birth cause severe cardiovascular and neurological effects ( Elkhier et al., 2017 ). Previous studies reported bromocriptine (0.2 or 0.6 mg rat-1 d-1) was injected daily during the last 5 or 12 d of estrogen treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Bromocriptine is used to treat infertility, hypogonadism, and ovarian hyperstimulation syndrome, benign tumors produced in the pituitary gland, adrenal gland, and thyroid gland. In reviewing 2014, it was shown that bromocriptine used to suppress milk production after birth cause severe cardiovascular and neurological effects ( Elkhier et al., 2017 ). Previous studies reported bromocriptine (0.2 or 0.6 mg rat-1 d-1) was injected daily during the last 5 or 12 d of estrogen treatment.…”
Section: Introductionmentioning
confidence: 99%